2004
DOI: 10.1530/eje.0.1510567
|View full text |Cite
|
Sign up to set email alerts
|

Early treatment with GH alone in Turner syndrome: prepubertal catch-up growth and waning effect

Abstract: Objective: In order to ascertain the advantages of early GH treatment in Turner syndrome (TS), we started a prospective study aimed at evaluating prepubertal height gain in a cohort of 29 girls who were treated with the same pro-kilo GH dose (1.0 IU/kg per week) since they were less than 6 years old and for at least 5 years before entering puberty. Patients and design: Following a minimum of 6 months of baseline observations, 29 girls with TS were enrolled for this prospective study provided that they (a) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…All 29 patients from our original study program (10) were included in the present study and fulfilled the …”
Section: Study Populationmentioning
confidence: 99%
“…All 29 patients from our original study program (10) were included in the present study and fulfilled the …”
Section: Study Populationmentioning
confidence: 99%
“…Though the optimal age for initiation of GH treatment has not been established [5], it is preferable not to start GH treatment later than five years of age, because the height of the majority of girls with TS usually drops below the fifth percentile of the normal girl growth curve between two and five years of age [1]. Many studies on GH treatment in girls with TS have established the importance of age at treatment initiation for long-term height gain [6][7][8][9][10][11][12][13][14]. Moreover, a recent study has shown that early GH treatment could normalize height in infants and toddlers with TS, and restoration of height close to the average would mitigate the potential detrimental effects of short stature during childhood and allow for age-appropriate initiation of feminization [15].…”
mentioning
confidence: 99%
“…Like Wasniewska et al (1) we also have an interest in the effect of growth hormone (GH) on growth and final adult height in Turner syndrome. Predicting final adult height in any individual is far from an exact science, but we believe that Wasniewska's calculations are flawed; first due to the inappropriate use of height standard deviation scores (SDS), and secondly due to the fact that the girls in their study, after their initial measurement, were being treated with GH.…”
mentioning
confidence: 94%
“…As such, it is likely that the girls in this study treated with GH will be growing very differently to the untreated girls from which the Lyon equation is derived. We believe that these two key points may have influenced the accuracy of the prediction of adult height by Wasniewska et al (1).…”
mentioning
confidence: 95%